2022
DOI: 10.34035/jk.v13i1.806
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Dimensi Reliability Pada Persepsi Dan Kepuasaan Pasien Anc Di Puskesmas Wilayah Surakarta

Abstract: Persepsi kualitas pelayanan berhubungan dengan kepuasan pasien. Pelayanan Antenatal Care yang berkualitas dapat memberikan pelayanan yang dibutuhkan ibu hamil sehingga resiko tinggi atau komplikasi dapat dicegah sejak dini. Pelayanan yang diberikan oleh tenaga kesehatan untuk ibu hamil sesuai dengan standar pelayanan ANC yang telah ditetapkan minimal 4 kali selama hamil (1 kali pada trimester pertama, 1 kali pada trimester kedua dan 2 kali pada trimester ketiga). Di dalam dimensi reliability mencangkup kemampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A research by Chang and Chen also found chamomile tea was beneficial to improve sleep quality and reduce stress, as PSQS score decreasing, in postpartum mother (Chang & Chen, 2016). Other studies found chamomile aromatherapy could reduce prevalence of insomnia in student and elderly (Khasanah, 2020) (Fitriana et al, 2019).…”
Section: Chamomile Aromatherapy Interventionmentioning
confidence: 95%
See 1 more Smart Citation
“…A research by Chang and Chen also found chamomile tea was beneficial to improve sleep quality and reduce stress, as PSQS score decreasing, in postpartum mother (Chang & Chen, 2016). Other studies found chamomile aromatherapy could reduce prevalence of insomnia in student and elderly (Khasanah, 2020) (Fitriana et al, 2019).…”
Section: Chamomile Aromatherapy Interventionmentioning
confidence: 95%
“…Carminative effect contained in its essential oil split into smaller particles. They act as calming and relaxing substance and initiate sleep process (Fitriana, 2019) (Khasanah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Respondents answered yes to the question "The midwife measures the mother's body temperature during a visit to carry out an examination". As we know that measuring body temperature is an important thing that must be done at every ANC visit as a management of early detection of complications that can occur in pregnant women and can harm pregnant women and the fetus (21).…”
Section: Reliabilitymentioning
confidence: 99%
“…Physical activity and light exercise such as gymnastics and muscle stretching therapy are important factors for maintaining the health of the elderly. The World Health Organization (WHO) guidelines recommend that older people aged 65 years or older should participate in at least 150 minutes of moderate-intensity aerobics throughout the week or do at least 75 minutes of vigorous-intensity activity throughout the week or an equivalent combination of the two (Khasanah et al, 2017). Progressive muscle relaxation is an alternative therapy that serves to reduce muscle tension, which can then relax muscles ranging from facial muscles to leg muscles.…”
mentioning
confidence: 99%